Bird odyssey - Hamby, Barbara, 1952- (Pitt poetry series., 2018)
Travel has always been Barbara Hamby's muse, and in Bird Odyssey she hits the road hard, riding a train across Siberia, taking a car trip from Memphis to New Orleans on Highway 61, and following The Odyssey from Troy to Ithaka. The concatenation of images released include Elvis and Tolstoy cruising through the sky in a pink Cadillac, Homer and Robert Johnson discussing their art in the Underworld, and the women in The Odyssey telling their side of the story, because what's a woman to do in this world of men? She has to strike out on her own, ask the right questions, and tell her own story, translating the world into her own bright lie.